The Legality of Nadzir Waqf Land Managerin Islamic Philanthropy Studies (A Case Study in Tampan, Pekanbaru City) - Andriko Andriko; Offiyardi Offiyardi (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: This research aims to find out the legality of nadzir as the manager of the waqf lands in Islamic philanthropy perspective of it.Design/Method/Approach: The report on the replacement and dismissal of nadzir to the office of religious affairs of Tampan is not properly performed; thus of the 212 population, the writer takes 5 nadzirs as a sample analysed descriptive qualitative analysis with purposive sampling technique.Findings: The research shows that none of nadzir reports the replacement and dismissal to the local office of religious affairs (KUA). The nadzirs only know that waqifs hand waqf land over to them to be used by muslim, but not for the matter of the replacement and dismissal. In other words, nadzirs in Tampan have not developed a professional sense of duty due to the lack of socialization from KUA.Originality/Values: Furthermore, the impact of  no report on retiring and shifted nadzir to KUA is mudharat in the system of administrations or report on waqf land. At worst, misuse of waqf land can occur. The report on the replacement and dismissal of nadzir in Tampan is inconsistent with article 221 of Law Number 41 of 2004. Verse 1 and 2 state that nadzir is obliged to report the replacement and dismissal of nadzir to local KUA.